A constituição identitária do sujeito dialógico na trilogia divergente de Veronica Roth - (:unkn) unknown (Universidade Federal de Goiás, 2020)
The present study aims to reflect on the identity construction of the dialogical subject Beatrice Prior, known as Tris, in the series Divergente, by Veronica Roth. Thus, in keeping with the proposed theme and purpose, the corpus consists of utterances chosen from the novels: Divergent – one choice can transform you (2012); Insurgent – one choice can destroy you (2013); and, Allegiant - one choice will define you (2014). The research is motivated in three areas: the academic, due to the fact that it examines the dialogicity of the utterance in the functioning of the novelistic language; the philosophical, for understanding that the sphere of the philosophy of language, in particular, guarantees a better and greater understanding as to the constitutive function of the word, of the language and of the speech in the multiple forms of discourse, here, the novel; and, the social, directed to Brazilian Basic Education, for favoring the engagement of children and adolescents in the universe of reading literary works, as well as in the construction of critical, reflective and autonomous readers about their own formation as a social subject. The study is also theoretically based on the theoretical conceptions of Bakhtin and the Circle, especially in the works: Marxism and philosophy of language: fundamental problems of the sociological method in the science of language (2017), by Volóchinov; Theory of the novel I: the stylistic (2015), by Bakhtin; Notes on literature, culture and humanities (2017a), by Bakhtin; The genres of discourse (2016), by Bakhtin; Utterance structure (s/a), by Voloshinov; Freudism: a critical sketch (2017b), by Bakhtin; Towards a philosophy of responsible action (2017c), by Bakhtin; among others. The research presents methodologically on the tripod of description-analysis-interpretation of utterances, through collation, and has a dialectical-dialogical approach, because from a socioideological perspective, it relates the utterance with the socio-cultural experience, the architectural foundation of a project to say subjects, set in peculiar chronotopes, mainly constituted by dialogical relations. In this sense, this study hypothesizes that the identity of Beatrice (Tris) is socially formed by the discursive interaction with the other characters, because it is a dialogic subject constructed in and by the language of the novels.
The identity constitution of the dialogical subject in Veronica Roth's divergent trilogy
Keywords: Trilogia divergente; Enunciado; Signo ideológico; Sujeito; Divergent trilogy; Utterance; Ideological sign; Subject; LINGUISTICA, LETRAS E ARTES::LETRAS